A Comparative Study Between the Use of Aqueous Extract of Ginger, Green Tea and a Saxenda Drug for Weight Loss in Male Albino Rats - Abduljaleel, Zainab Wisam (American Journal of Biology and Natural Sciences, 2025)
Background: Many weight reduction supplements, such as green tea and ginger, are based on herbal medicines and remedies that have been used for centuries in various parts of the world to maintain health and prevent or treat disease. Aim of study: comparative study between the combination effect of aqueous extract of ginger, Green tea with a saxenda drug against weight loss and Lipid profile , thyroid hormones, and hematological parameters in male albino rats: Material and Method: this study included 3 groups group 1 :a control group and was given food and water only, group III was given the Saxenda drug in concentration 6mg\ml for 20 days, group III was given the aqueous plant extract of each Ginger and green tea at a concentration 250 mg\kg for 20 days. At the end of the experiment, blood was conduct the following testsT3,T4,TSH, lipids profile, ALT,AST,ALP . The second part of the blood was received to conduct some blood tests, which included: RBC count, Hb and PCV. Results: there was a significant decreased in body weight in group treated with Saxenda drug (165.67 ±3.48) g and group treated with mix plants extract (161.33 ±3.38) with significant differences as well as ,the results revealed a significant decreased in T3 hormone in groups treated with Saxenda drug (71.20 ±3.19) ng/ml compared with treated group with mix extract (82.40 ±2.78) ng/ml ,also the results show significant increased in T4 hormone in groups treated with Saxenda drug (9.06 ±0.25) ug\ml and mix plant extract (8.33 ±0.43) ug\ml compared control group moreover there was decrease in lipid profile in plant extract group compared with and Saxenda group but no significant difference, however liver enzyme ALT, AST, ALP increased in aqueous extract of the plants group (23.67 ±2.73, 27.33 ±2.72, 85.67 ±4.09) respectively , the level RBC,HB, PCV in group treated with aqueous extract (4.81 ±0.28 , 12.72 ±0.46, 36.67 ±1.20) respectively increased compared with Saxenda with significant difference but there was no significant with control group. Conclusion: both green tea and ginger extract showed improvement in reduce the body weight as well improvement in thyroid hormones and blood parameter, the results showed both green tea and ginger extract has protective effect depending on liver enzyme levels.